Tinjauan Pelaksanaan Retensi Sesuai Dengan Permenkes Ri No. 269 Tahun 2008 Dan Akreditasi Snars Di Rsud Kanjuruhan Kabupaten Malang - Nurfitria Dara Latuconsina; Tiara Chandra Dewi; Andy Susantyo (Kampurui Jurnal Kesehatan Masyarakat, 2019)
Retention of medical record documents is an activity separating active medical record documents with medical record documents inactive by looking at the period of storage medical record documents. Implementation of retention in Kanjuruhan Hospital Malang Regency carried out gradually starting from sorting, moving, and destroying but the processes don’t use Records Retention Schedule, the storage of inactive medical record documents overload and the absence of a special shelf to store the documents and the absence of special officers for carrying out medical record documents retention. The purpose of study was to find out The Retension to Conform Permenkes RI No. 269 Year 2008 and Standards of Accreditation of SNARS in RSUD Kanjuruhan Malang Regency. This research method was descriptive with a qualitative approach. The informants in this study were 1 key informant and 2 regular informants. Data collection techniques were interview observation and documentation study. Based on research results in Kanjuruhan Hospital Malang Regency, the process of implementing retention don’t use the Records Retention Schedule to determine the period of storage of medical record documents. The retention process wasn’t accordance with the existing SPO. The process of implementing retention wasn’t in accordance with Permenkes RI No. 269 Year 2008 because there was no special officer carrying out the retention process. The process of implementing retention wasn’t in accordance with Accreditation of SNARS MIRM 10 because there was no special shelf for storing medical record documents and one of the officers still didn’t understand the contents of the accreditation standards.